Positive Psychology and Strengths-Based Interventions (SBIs): Implications for Uses with Special Student Populations (Special Needs, P-3, Gifted) - Christian E. Mueller; Xu Jiang; Denise L. Winsor (MDPI AG, 2024)
In 2000, Seligman and Csikszentmihalyi published the highly influential "Positive Psychology: An Introduction" in American Psychologist, and with it, they advocated for a strengths-based approach for helping people live a "good life". Building on that work, positive psychology was further conceptualized as consisting of meta-psychological and practical aspects. The meta-psychological constitutes the aims or "grand vision" of what positive psychology stands for, whereas the practical constitutes the "nuts-and-bolts" elements that should be focused on in developing interventions. In the present commentary, we build on this previous work to propose a "positive psychology pragmatic framework" to develop strengths-based interventions (SBIs) for use with special student populations; in this case, students with special needs and P-3 and gifted students. Relatedly, we review the empirical and theoretical/conceptual literature relevant to the use of SBIs within each subpopulation as well as discuss some characteristics that make each subpopulation unique. Consequently, to the highest degree possible, we advocate for integrating intrapersonal, interpersonal, contextual/environmental, systemic, and developmental factors in developing SBIs and we make specific recommendations for future research through the lens of this proposed framework.